Antimicrobial Activity of Temu Blenyeh (Curcuma purpurascens Blume) Ethanol Extract Against on Streptococcus mutans and Candida albicans: bahasa indonesia - okta, Oktariani Pramiastuti; Laili, Ratna Tika Nikhmatul (Ad-Dawaa’ Journal of Pharmaceutical Sciences, 2023)
Introduction: Temu blenyeh (Curcuma purpurascens Blume) is a species of Curcuma belonging to the Zingiberaceae family. This plant contains secondary metabolites such as flavonoids, alkaloids, terpenoids, saponins, tannins, and polyphenols, which function as antimicrobials. Aims: The aims of this study was to determine the antimicrobial activity of the ethanol extract of intersection blenyeh against Streptococcus mutans and Candida albicans. Methods: The extraction process was carried out by maceration, and the antimicrobial activity test was carried out using paper disc diffusion. The negative control used in this study was 5% DMSO, while the positive control was 0.2% Chlorhexidine. Result: The results of phytochemical screening using the TLC method showed that the ethanol extract of intersection blenyeh contained flavonoids, alkaloids, terpenoids, saponins, tannins, and polyphenols. The results of the antimicrobial activity test of the ethanol extract of the temu blenyeh at concentrations of 30; 40; 50; 60; and 70% against Streptococcus mutans produced an inhibition zone belonging to the medium category with an average inhibition zone value of 6.75; 7.00; 7.08; 7.16; and 8.26 mm, while Candida albicans produced an inhibition zone that belonged to the very weak category with an average inhibition zone value of 2.75; 3.16; 3.33; 3.60; and 3.67 mm. Conclusion: The conclusion of this research is that the ethanol extract of intersection blenyeh has antimicrobial activity against Streptococcus mutans and Candida albicans.